Fabrication of Cellulose Powder Dielectric Composite Material using Pineapple Leaves Fiber - Giamasrow, Rudraa Devi; Nurhafizah, Abu Talip Yusof; Azahani Natasha, Azman; Norazwina, Zainol; Mohamad Shaiful, Abdul Karim (Semarak Ilmu Publishing, 2024)
Pineapple, known for its delicious taste and nutritional value, generates substantial waste in the form of cores, leaves, and skin, resulting in significant yearly accumulations. Efficient disposal of pineapple waste has become a critical challenge due to its increasing production and potential environmental pollution. The objective of this paper is to volarize natural fiber derived from pineapple waste by fabricating it into a new dielectric composite material. The fabrication process of dielectric composite material was achieved by using the optimization technique through Design Expert software, resulting in noteworthy findings. Then, the properties of the fabricated materials were analyzed in terms of their permittivity value and elemental composition. The permittivity value of the newly fabricated dielectric materials was measured using the vector network analyzer (VNA) method, while their elemental composition was characterized using energy-dispersive X-ray (EDX) spectroscopy. The correlation between elemental composition and the permittivity value of newly fabricated composite materials is analyzed in this paper. As a result, the dielectric composite material attained its highest permittivity (4.08) when composed of 76.02% carbon and 22.61% oxygen. Conversely, the material exhibited a lower permittivity value (2.87) when its carbon content decreased to 69.32% and its oxygen content increased to 29.81%. This outcome highlights the crucial role of carbon in absorbing and storing electromagnetic signals, influencing the dielectric properties of the material. In conclusion, this paper unveils a ground-breaking use for waste pineapple leaves, showcasing how their carbon content significantly affects the resulting dielectric composite material's permittivity. This innovative eco-friendly material presents a sustainable alternative for non-recyclable dielectric materials in electronic devices such as PCBs, antennas, and sensors, for example.